2003
DOI: 10.1183/09031936.03.00014703
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in idiopathic pulmonary fibrosis suggest an important role for TGF‐β and IL-10

Abstract: Modulation of cytokine expression represents a potentially useful approach for the treatment of idiopathic pulmonary fibrosis (IPF).To identify potential targets for such intervention, semi-quantitative reverse transcriptasepolymerase chain reaction was used to compare the expression of messenger ribonucleic acids (mRNAs) coding for 17 cytokines in lung tissue obtained from patients with IPF at the time of diagnosis and control subjects. Some cytokines were also studied at the protein level by immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
81
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(97 citation statements)
references
References 32 publications
11
81
0
5
Order By: Relevance
“…The predominant role of IL-10 is to reduce inflammation. However, increased expression of IL-10 significantly contributes to fibrosis (Bergeron et al, 2003;Barbarin et al, 2005). The present study also showed that treatment with NS-398 significantly decreased mRNA levels of TGF-␤1 and CTGF, which was again reversed by the EP 2 receptor agonist.…”
supporting
confidence: 58%
“…The predominant role of IL-10 is to reduce inflammation. However, increased expression of IL-10 significantly contributes to fibrosis (Bergeron et al, 2003;Barbarin et al, 2005). The present study also showed that treatment with NS-398 significantly decreased mRNA levels of TGF-␤1 and CTGF, which was again reversed by the EP 2 receptor agonist.…”
supporting
confidence: 58%
“…60) and subsequent fibrosis (61)(62)(63). On the other hand, Th1 cytokines such as TNF-a, IFN-g, and IL-2, which are known to act antifibrotically (61,64,65), were reported to annul resistance to Fas-induced apoptosis by a mechanism involving c-FLIP downregulation (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b is fundamental to the pathogenesis of pulmonary fibrosis (Figure 2A) (50,(53)(54)(55)(56). In the lung, TGF-b is expressed by multiple cell types, including epithelial cells, macrophages, and fibroblasts, and levels are elevated in animal models and in patients with IPF (57)(58)(59)(60). Pulmonary expression of TGF-b is sufficient to induce progressive fibrosis in rodents (61); conversely, blocking TGF-b signaling inhibits fibrosis in rodent models (62,63).…”
Section: Pulmonary Fibrosismentioning
confidence: 99%